Analisis Kesalahan Berbahasa pada Penulisan Karangan Narasi Siswa Kelas V SDN 1 Kramatwatu: The analyzing of Language Error in Narative Writting Skills at Student of Fifth Class of SDN 1 Kramatwatu - Atiqa Sabardila (TOTOBUANG, 2022)
Indonesian language learning is learning that has the objective of optimizing students' writing skills. Writing skills are individual skills in expressing ideas, feelings, and opinions to others through written language. However, the fact is that when pouring their thoughts and feelings into an essay, students still make mistakes. Therefore, this study aims to describe the forms of language errors in the narrative essays of fifth-grade students at SDN Kramatwatu. The data collection method carried out the observing the noting. The analyzing methods use the referential equivalent method with the basic technique of sorting referential. The results of the analysis find language errors in the fields of phonology, morphology, syntax, semantics, and spelling. Error occur in phonology include 1) omission of phonemes, 2) addition of phonemes, and 3) replacement of phonemes. The findings of language errors in the field of morphology include 1) prefix affix errors, 2) confix affix errors, 3) preposition errors, 4) noun replacement errors, and 5) verb replacement errors. Syntax Errors occurred in the irregularly structured sentences, improper use of conjunctions, redundant use of words, and 4) preposition selection errors. Findings of language errors in the field of semantics include deviations in meaning. Language errors in the spelling were 1) errors in the use of capital letters and 2) errors in the use of punctuation marks. Keywords:Â language errors, writing, narrative essay, elementary school